Technical Assessment of the Affymetrix Yeast Expression GeneChip YE6100 Platform in a Heterologous Model of Genes That Confer Resistance to Antimalarial Drugs in Yeast - Nau, Martin E. (American Society for Microbiology, 2000)
The advent of high-density gene array technology has revolutionized approaches to drug design, development, and characterization. At the laboratory level, the efficient, consistent, and dependable exploitation of this complex technology requires the stringent standardization of protocols and data analysis platforms. The Affymetrix YE6100 expression GeneChip platform was evaluated for its performance in the analysis of both global (6,000 yeast genes) and targeted (three pleiotropic multidrug resistance genes of the ATP binding cassette transporter family) gene expression in a heterologous yeast model system in the presence and absence of the antimalarial drug chloroquine. Critical to the generation of consistent data from this platform are issues involving the preparation of the specimen, use of appropriate controls, accurate assessment of experiment variance, strict adherence to optimized enzymatic and hybridization protocols, and use of sophisticated bioinformatics tools for data analysis.